Foreign Aid to Higher Education During the SDGs: Leaving Many Behind - Heleta, Savo; Cochrane, Logan; Al-Mannai, Salwa (International Higher Education, 2025)
<h3 id="the-sustainable-development-goals-are-framed-around-the-notion-of-leaving-no-one-behind-and-prioritizing-those-most-marginalized-these-objectives-are-not-being-met-for-higher-education-due-to-the-prioritization-of-international-scholarship-aid-and-the-comparative-neglect-of-other-types-of-support-for-higher-education-in-countries-requiring-assistance-changes-are-needed-by-2030-and-strengthening-higher-education-in-lower-income-countries-needs-to-be-a-priority-of-the-post-2030-global-development-plan" data-pm-slice="1 1 []">The Sustainable Development Goals are framed around the notion of leaving no one behind and prioritizing those most marginalized. These objectives are not being met for higher education due to the prioritization of international scholarship aid and the comparative neglect of other types of support for higher education in countries requiring assistance. Changes are needed by 2030, and strengthening higher education in lower-income countries needs to be a priority of the post-2030 global development plan.